KEMAMPUAN PEMAHAMAN KONSEP MATEMATIKA SISWA TERHADAP MATERI HIMPUNAN DI KELAS VII - Wahyuni, Selly; Hartoyo, Agung; Suratman, Dede (UNIVERSITAS TANJUNGPURA, 2023)
This study aims to understand the obstacles of seventh grade students of SMP Negeri 1 Jawai Selatan in understanding numerical ideas on set material in class VII SMP Negeri 1 Jawai Selatan. The subjects in this study were students of class VII A SMP Negeri 1 Jawai Selatan which amounted to 31 students. Taking class VII as the subject depends on the approval of the school and the replacement students have gotten the material set at the junior high school level. The object of consideration is the test scores. Negeri 1 Jawa Selatan. In general, students' ability to understand numerical ideas in set material is at a moderate level, and this implies that students currently have a fairly good understanding of set material. The highest capacity is at the pointer of repeating set ideas with a level of 74% which is in the high classification, and it indicates that understudies can repeat the idea, while the lowest capacity is at the pointer of creating basic or adequate conditions with a level of 18% which is in the low classification, and it indicates that not many understudies can create basic or adequate conditions. In general, the ability of understudies to understand numerical ideas in set material is in the medium classification with a level of 47.5%.